Sleeping-tree fidelity of the spider monkey shapes community-level seed-rain patterns in continuous and fragmented rain forests. (8th June 2015) - González-Zamora, Arturo; Arroyo-Rodríguez, Víctor; Escobar, Federico; Oyama, Ken; Aureli, Filippo; Stoner, Kathryn E.
Abstract: Repeated use of sleeping trees (STs) by frugivores promotes the deposition and aggregation of copious amounts of seed, thus having key implications for seed dispersal and forest regeneration. Seed-rain patterns produced by this behaviour likely depend on the frequency of use of these sites, yet this hypothesis has been poorly tested. We evaluated community-level seed-rain patterns produced by the spider monkey (Ateles geoffroyi) over 13 mo in latrines located beneath 60 STs in the Lacandona rain forest, Mexico. Because this primate is increasingly 'forced' to inhabit fragmented landscapes, we tested whether sleeping-tree fidelity (STF) differed among sites and between continuous and fragmented forests. We also tested whether seed-rain patterns were associated with STF within each site and forest type. STF was highly variable among STs (average = 7 mo, range = 1–12 mo), but did not differ among study sites or forest types. STF was positively associated with seed abundance, species diversity and species turnover. Nevertheless, STF tended to be negatively related to seed community evenness. These results are likely due to the most frequently used STs being in areas with greater food density. Our results demonstrate that site fidelity shapes community-level seed-rain patterns and thus has key ecological implications.